2009
DOI: 10.1186/1743-422x-6-109
|View full text |Cite
|
Sign up to set email alerts
|

The role of NH4Cl and cysteine proteases in Human Papillomavirus type 16 infection

Abstract: We present data that suggest HPV16 infection is in part mediated by cysteine proteases, and that NH4Cl blocks the intracellular trafficking of infectious viral particles. To our knowledge this is the first demonstration that cysteine proteases influence the infection of a non-enveloped virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
4
29
1
Order By: Relevance
“…In line with previous studies (23,30,32,33), most of the proteolytic processing occurred in endolysosomes by cysteine cathepsins. Dispensable for infection, the cathepsin-mediated cleavages were likely the result of postuncoating L1 degradation and, in part, of an autophagic response to infection.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In line with previous studies (23,30,32,33), most of the proteolytic processing occurred in endolysosomes by cysteine cathepsins. Dispensable for infection, the cathepsin-mediated cleavages were likely the result of postuncoating L1 degradation and, in part, of an autophagic response to infection.…”
Section: Discussionsupporting
confidence: 77%
“…The role of cysteine cathepsins in HPV entry has been previously analyzed with different results (23,32,33). Although two studies suggested a cathepsin-mediated cleavage of L1, Dabydeen and Meneses (33) claimed a productive role for it in virus uncoating, whereas Calton and colleagues (32) suggested a role for postuncoating degradation.…”
Section: Hpv16 L1 Is Proteolytically Cleaved During Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the potential receptors and the mode of endocytosis are still highly questionable, a majority of studies agree that exposure to low pH in late endosomes or lysosomes is critical for viral uncoating and, consequently, for efficient PV infection (3,5,8,19). In the case of the HPV-16 L2 interaction with SNX17, this seems to aid lysosomal escape (12).…”
mentioning
confidence: 99%
“…We concluded that the infectivity of MCV is in general not affected by SNX17 silencing, suggesting that the observed reduction in PV infectivity following SNX17 silencing is directly related to the interaction between L2 and SNX17. While the potential receptors and the mode of endocytosis are still highly questionable, a majority of studies agree that exposure to low pH in late endosomes or lysosomes is critical for viral uncoating and, consequently, for efficient PV infection (3,5,8,19). In the case of the HPV-16 L2 interaction with SNX17, this seems to aid lysosomal escape (12).…”
mentioning
confidence: 99%